A descriptive study of the prevalence of Acute Foot and Ankle complaints/injuries of adults attending a public sector secondary hospital orthopaedic clinic in South Africa over a 12-week period - Dlamini, Njabulo Knowledge (Department of Human Biology, 2025)
BACKGROUND: Orthopaedic trauma places a substantial cost burden on health systems around the world, and may also lead to mobility impairment, disability, and chronic pain in patients, especially when affecting the foot and ankle. The epidemiology of foot and ankle injuries has previously not been well reported in South Africa. In order to gain a greater understanding into the degree of health burden represented by conditions of the foot and ankle as well as the associated risk factors and types of injury, we aimed to describe and evaluate the patient population presenting at a public health hospital over a specified time period. Insights into the epidemiology specific to the South African context may aid health care resource planning and contribute to improved patient care. METHODS: A prospective, descriptive study was conducted to determine the prevalence, characteristics and risk factors of adults presenting to the orthopaedic acute clinic at Prince Mshiyeni Memorial Hospital with acute foot and ankle complaints/injuries between December 2022 to March 2023 (12-week period). Demographic (sex, age, height, weight, BMI) and clinical (type of injury, pain scores, management) data were collected and analysed using percentages, Mann-Whitney U Test, t test and Chi-square analysis. RESULTS During the 12-week period, 14% of the 615 lower limb cases were referred for Foot and Ankle injuries specifically. The cohort comprised 80 participants with an average age of 43 years with 64% (n=51) (being) female. Ankle fractures were the most common presenting injury (54%), with females more affected than males, 31 (61%) vs.12 (41%)) respectively. Males suffered more foot fractures than females, 12 (41%) vs. 5 (10%) respectively (p< 0.05). Foot fractures represented 21% of all foot and ankle injuries. Ankle sprains made up 15% of all injuries which interestingly was similar to that of midfoot sprains (15%). The highest number of injuries were noted within the age range 30-39 (34%) with no significant difference noted between sex and age presentation, but a significant difference was noted for mechanism of injury and sex (p< 0.001), no significant differences were noted for BMI between the sexes with a median of 25kg.m2 for both. Low energy fall was the most common mechanism of injury described affecting 66% of all participants and 74% (39) of females. Road traffic accidents (RTA) accounted for 21% (17) and direct trauma/assault 6% (5) of all mechanisms of injury. Fifty percent (40) of participants were managed conservatively by means of plaster of Paris, 40% (32) with plaster backslab, and 6% (5) admitted for surgical intervention. CONCLUSION: Foot and ankle pain is a prevalent problem which constitutes a high number of traumatic bony and soft tissue injuries. Within this cohort, more females presented with ankle fractures and males with foot fractures, with the 30-39-year age group most affected. Low energy fall mechanisms were most commonly reported within females, while males suffered more direct trauma and sports injury-related mechanisms. Only a small percentage of patients were admitted for surgery. The researchers recommend more epidemiological studies across major trauma centres with greater participant numbers and longer follow up to give a better scope into the full extent of the burden of foot and ankle pain/injuries in South Africa, and expand database registrations, hereby impacting policy making and budget allocation to improve patient care and outcomes